Selected anthropometrical, muscular architecture, and biomechanical variables as predictors of 50-m performance of front crawl swimming in young male swimmers - Nasirzade, A.; Ehsanbakhsh, A.; Argavani, H.; Sobhkhiz, A.; Aliakbari, M. (Science & Sports, 2014)
Background: Swimming performance may be influenced by anthropometric, physiology and biomechanical factors. Purpose: The purpose of this study was to examine the influence of different parameter on 50-m front crawl swimming performance in young male swimmers. Methods: Selected anthropometrical (body height, body mass, body mass index, arm span, shoulders width, thigh, leg, and upper arm lengths), muscle architectural (muscle thickness (MT), pennation angle (PA), and fascicle length (FL)), and biomechanical (stroke rate (SR), stroke length (SL), and stroke index (SI)) parameters have been measured on 50-m front crawl swimming performance in young male swimmers 13.86 ± 0.86 years of age (n = 23). Results: Stepwise regression analysis revealed that biomechanical parameters (84%) characterized best 50-m front crawl swimming performance, followed by muscular architecture (52%) and anthropometrical (22%) parameters. Also, SI, SL, and MT of Vastus Lateralis (VL) explained 89% of 50-m front crawl swimming performance variability in these young male swimmers. Conclusion: These results suggest that 50-m front crawl swimming performance can be generally explained by biomechanical and muscular architecture parameters than anthropometrical factors in young male swimmers.